Evaluasi Jalan Angkut untuk Produksi Penambangan Area Pit 6 B Pada PT Jhonlin Baratama Kalimantan - Asmiani, Nur; Widodo, Sri; Usman, Arfa (CV Insight Publisher, 2023)
Road access is an important factor in the achievement of coal and OB transport targets. Therefore, transport activities must be accompanied by road conditions that are suitable to be used as production routes in accordance with the standards adopted by Bina marga and AASTHO. The purpose of this study is to determine the geometry of mining road and the supporting factor of smoothness and safety at PT. Jhonlin Baratama. The data used in this study are data of road haul road, radius and superelevation, cross slope and road slope. After this data is obtained then processed using software Minescape 5.7 to obtain the count of road length, road width, and elevation. MS Software. Excel to know the evaluation data of high difference, road grade, cross slope, radius and superelevation. Processed data were analyzed based on standards of Bina marga and international AASTHO to determine the feasibility of road geometry. From the results of study that has been done, it is known that the existing haul road already meets the minimum width requirement for a straight road that is 9 m for Hino 320 and 19 m for HD465-7. On the two-lane haul road and on the bend, for Hino 320 already meets the minimum width standard whereas for HD 465-7 it is necessary to add the width of the bend in segment C, F, G, H and I the width addition is intended to prevent dump truck waiting when passed. There are also some road segments whose slope exceeds the standard, which is 8% and does not have a cross slope that has the potential to cause puddles.